Functional Selectivity Does Not Predict Antinociceptive/Locomotor Impairing Potencies of NOP Receptor Agonists - Azevedo Neto, Joaquim; Ruzza, Chiara; Sturaro, Chiara; Malfacini, Davide; Pacifico, Salvatore; Zaveri, Nurulain T.; Calò, Girolamo (Frontiers in Neuroscience, 2021)
Nociceptin/orphanin FQ controls several functions, including pain transmission, via stimulation of the N/OFQ peptide (NOP) receptor. Here we tested the hypothesis that NOP biased agonism may be instrumental for identifying innovative analgesics. In vitro experiments were performed with the dynamic mass redistribution label free assay and the NOP non peptide agonists Ro 65-6570, AT-403 and MCOPPB. In vivo studies were performed in wild type and β-arrestin 2 knockout mice using the formalin, rotarod and locomotor activity tests. In vitro all compounds mimicked the effects of N/OFQ behaving as potent NOP full agonists. In vivo Ro 65-6570 demonstrated a slightly higher therapeutic index (antinociceptive vs motor impairment effects) in knockout mice. However, all NOP agonists displayed very similar therapeutic index in normal mice despite significant differences in G protein biased agonism. In conclusion the different ability of inducing G protein versus β-arrestin 2 recruitment of a NOP agonist cannot be applied to predict its antinociceptive versus motor impairment properties.